To sew or not to sew - Chaitali Hambire; Umesh Vishnu Hambire (Wolters Kluwer Medknow Publications, 2024)
Tongue injuries in children vary from slight lacerations to complete amputation. It could be due to falls, self-mutilation, epilepsy, child abuse, or sports injuries. The anterior dorsum is the most common site, followed by the mid dorsum and anterior ventral part. These injuries may cause dysfunction of the tongue, hemorrhage, and disfigurement. Management of injuries of the tongue in young children is challenging. There are no established guidelines for managing tongue lacerations. This is a case report of a 3-year-old girl with a laceration on the anterolateral part of the tongue with nonapproximating wound edges. The laceration extended from the dorsal to the ventral part. The parents were apprehensive for the surgical management of the injury due to the age of their daughter. Hence, healing of the injury with conservative management without suturing was achieved. The management of traumatic injuries of the tongue in children is difficult due to their age and cooperation. The pediatrician has to decide whether to heal the tongue by primary or secondary intention. Our decision to allow the healing by secondary intention was successful. The tongue healed without any complications, barring a small scar, with satisfactory esthetic and functional outcome. Both the parents and the child were satisfied with the management of the injury.